Advancements and Ethical Challenges in Data Analytics : Transforming Research, Decision-Making, and Business Strategy - Dr. Dipikaben Umakant Thakar; Dr. Bhawesh Kumawat; Dr. Darshanaben Dipakkumar Pandya (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Data analytics is now the central field of study in research, led by the explosive growth of data coming from many sources. This article investigates the background of data analytics from the challenge of handling large data and the significance of data engineering. We then consider basic processes such as data cleansing, transformation, and modeling. Various methods of analysis, including exploratory data analysis, predictive modeling, and machine learning, are explained. We also highlight the programming languages and software that are most commonly used in data analytics. The paper then goes on to explain recent advancements in the discipline, including big data, cloud computing, and data privacy. Lastly, this comprehensive review is meant to enable researchers to make use of data analytics to gain useful insights from their data.